Philosophy, Theory or Way of Life? Controversies in Antiquity, the Middle Ages and the Renaissance : With a Foreword by Pierre Hadot - Domański, Juliusz, (Philosophy as a Way of Life ;, 2024)
Philosophy in antiquity was conceived not as mere theory but as a way of life; but it lost its 'practicist' cast through a process that begins in the patristic era and peaks with its conversion into an academic discipline in the medieval univers